2006
DOI: 10.1182/blood-2006-02-002824
|View full text |Cite
|
Sign up to set email alerts
|

Biologic pathways associated with relapse in childhood acute lymphoblastic leukemia: a Children's Oncology Group study

Abstract: Outcome for children with childhood acute lymphoblastic leukemia (ALL) who relapse is poor. To gain insight into the mechanisms of relapse, we analyzed gene-expression profiles in 35 matched diagnosis/relapse pairs as well as 60 uniformly treated children at relapse using the Affymetrix platform. Matched-pair analyses revealed significant differences in the expression of genes involved in cell-cycle regulation, DNA repair, and apoptosis between diagnostic and earlyrelapse samples. Many of these pathways have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
131
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(139 citation statements)
references
References 35 publications
6
131
2
Order By: Relevance
“…2,[5][6][7]13,[35][36][37] Relatively few studies have focused on relapse samples and we are aware of only three previous studies using matched diagnosis-relapse pairs to better understand the process of relapsed ALL. 5,6,18 One of these studies was a small pilot study we performed a few years ago using seven patient pairs; 18 the other two are larger studies, one Australian (Beesley et al 5 ) and the other American (Bhojwani et al 6 ), who studied 11 and 35 matched diagnosis-relapse samples, respectively, and additional diagnosis samples. Although both seminal studies were performed carefully, they found only small numbers of genes to be differentially expressed between diagnosis and relapse samples, in general with changes that were relatively small (1.5-to 2-fold per gene), which are not easily interpreted in terms of mechanisms underlying the relapse process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2,[5][6][7]13,[35][36][37] Relatively few studies have focused on relapse samples and we are aware of only three previous studies using matched diagnosis-relapse pairs to better understand the process of relapsed ALL. 5,6,18 One of these studies was a small pilot study we performed a few years ago using seven patient pairs; 18 the other two are larger studies, one Australian (Beesley et al 5 ) and the other American (Bhojwani et al 6 ), who studied 11 and 35 matched diagnosis-relapse samples, respectively, and additional diagnosis samples. Although both seminal studies were performed carefully, they found only small numbers of genes to be differentially expressed between diagnosis and relapse samples, in general with changes that were relatively small (1.5-to 2-fold per gene), which are not easily interpreted in terms of mechanisms underlying the relapse process.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18] Microarray technology can also provide an unbiased means to identify genes involved in the emergence of resistant leukemic clones. [5][6][7] For the identification of molecular mechanisms involved in relapse of ALL, pairwise comparison of matched diagnosis and relapses is, in principle, the most straightforward way to identify such genes. Several groups, including ours, have previously conducted such analyses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For preB-ALL, two recently published array sets 25,26 with matched pediatric diagnosis --relapse patients were analyzed. The use of matched diagnosis --relapse samples affords several advantages over a conventional cohort; it not only lends itself to the identification of genetic pathways and molecular mechanisms involved in relapse but also provides insights into the origins of the relapsed clone.…”
Section: Fat1 Expression Is Found In Leukemia Cell Lines But Not In Pmentioning
confidence: 99%